LANGUAGE AND IDENTITY IN CYBERSPACE. A MULTIDISCIPLINARY APPROACH - COTOC, Alexandra (Presa Universitară Clujeană, 2017)
The Internet and the digital world have created new opportunities for realtime conversations among individuals who are geographically dispersed, but who are sitting at their computer keyboards or are using other electronic devices. People post discourses and participate in “written” conversations in the new linguistic genre, which combines characteristics of both written and oral language, but also features specific to the digital environment. They type their messages in chat exchanges, and these messages appear on the screens of their interlocutors, preceded by the sender’s cybername (name or nickname) (see Bechar-Israeli, 2006); they register and create profiles on social network sites, blogs and game platforms.